2012
DOI: 10.1021/cb200511t
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Analogues of GalNAc as Substrates for Enzymes of the Mammalian GalNAc Salvage Pathway

Abstract: Changes in glycosylation are correlated to disease and associated with differentiation processes. Experimental tools are needed to investigate the physiological implications of these changes either by labeling of the modified glycans or by blocking their biosynthesis. N-Acetylgalactosamine (GalNAc) is a monosaccharide widely encountered in glycolipids, proteoglycans, and glycoproteins; once taken up by cells it can be converted through a salvage pathway to UDP-GalNAc, which is further used by glycosyltransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
7
32
0
Order By: Relevance
“…In addition, our accompanying paper (5) demonstrates that UDP-GlcNGc can also successfully enter the O-GlcNAcylation pathway resulting in O-GlcNGc modifications. We found GalNGc to be incorporated into O-glycans as also reported very recently by another group (36,37). Going beyond these published reports, we also isolated cellular O-glycans from cells grown in the presence of either GalNAc or GalNGc and performed structural analyses using mass spectrometry.…”
Section: Exogenous Galngc Incorporates As Glcngc Into Cellularsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, our accompanying paper (5) demonstrates that UDP-GlcNGc can also successfully enter the O-GlcNAcylation pathway resulting in O-GlcNGc modifications. We found GalNGc to be incorporated into O-glycans as also reported very recently by another group (36,37). Going beyond these published reports, we also isolated cellular O-glycans from cells grown in the presence of either GalNAc or GalNGc and performed structural analyses using mass spectrometry.…”
Section: Exogenous Galngc Incorporates As Glcngc Into Cellularsupporting
confidence: 83%
“…Future studies will reveal the impact of media supplemented GalNAc derivatives onto the overall complexity of O-glycan structural diversity in cells. After this study was finalized, another research group showed predominantly by lectin binding analyses that various artificial GalNAc derivatives, including GalNGc, seem to incorporate into O-glycans via the GalNAc salvage pathway (36,37).…”
Section: Exogenous Galngc Incorporates As Glcngc Into Cellularmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm this result, we subjected 6AzGlcNAc (Scheme S3A and Figures S13–S15 (SI) for details of synthesis and characterization) to in vitro phosphorylation by recombinant GalK2. 36 Specifically, GalK2 was incubated with 40 mM concentrations of GalNAc, GlcNAc, or 6AzGlcNAc and [ 32 P]γATP (5 mM). At these elevated substrate-concentrations, GalK2 readily phosphorylated both GalNAc and GlcNAc but gave no detectable modification of 6AzGlcNAc (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic labeling to enable selective photocrosslinking of O-GlcNAc-modified proteins to identify their binding partners (Yu et al, 2012d) Glycopeptides, glycoproteins R-, L-TOF Evaluation of GalNAc analogues as substrates for enzymes of the mammalian GalNAc salvage pathway (Pouilly et al, 2012b) Glycoproteins TOF/TOF (Hart et al, 2011) Human -defensin TOF (sinapinic), peptides…”
Section: Abbreviationsmentioning
confidence: 99%